The Dynamic Processes Mathematical Modeling in the Traction Coupling Device from Cars to the Trailers - Orysenko, Oleksandr; Scoryk, Maxym; Kryvorot, Anatolii; Shapoval, Mykola (International Journal of Engineering and Technology, 2018)
The dynamic processes mathematical modeling results in the traction car coupling with a trailer are presented. It is shown that the dissipative link presence in the coupling device prevents oscillation processes, and significantly reduces the dynamic loads during transient train movement. According to research, the design of a car trailer dynamic coupling device was proposed.Â Â Â